Thermoresponsive magnetic colloidal gels for in vitro cell expansion - Braim, Shwana (2016)
Recent studies and clinical trials have shown the potential of cell-based therapies for the treatment of a number of diseases and organ/ tissue damages. However, limited availability of some therapeutically important cells (i.e. adult stem cells) still remain as main challenges in the development of tissue engineering through to the clinic. Healthy cells are required in large numbers to form a tissue-engineered construct and primary cells must therefore be expanded in vitro for both scientific and clinical applications. Various strategies have been developed to expand cells in vitro with increasing emphasis on 3D matrices because it can provide microenvironments which more closely mimic in vivo systems. In this way the inherent difficulties associated with 2D culture such as loss of phenotype could be overcome. Moreover, 3D matrices provide higher surface areas to support expansion of larger cell numbers compared to monolayer culture. Although each 3D method has certain advantages, there is no single technique that can be used to produce material assemblies that address all the fundamental problems linked to 3D cell seeding (penetration into the scaffold), passaging (use of enzymes), and harvesting (cell yield). Recently, thermally reversibly-associating particles have been studied for the growth and support of multiple cell types and for delivery of therapeutic cells. But coupling of thermoresponsive properties to magnetic microspheres would enhance the 3D culture and expansion of multiple cell types, and facilitate rapid recovery of the expanded cell population by simple magnetic separation. In this study, it was proposed that the thermoresponsive properties would allow simple cell seeding at temperatures below the LCST of polymer stabiliser when the suspension is flowing and upon heating to above the LCST cells would be encapsulated and cultured within the particle gels (every cells surrounded by a number of particles, as the size of the particles are much smaller than the cells). The magnetic responsive property would allow efficient and scaffold free cell recovery after expansion without the need for using trypsin or enzymatic treatment. The ‘switchable’ component of reversibly associating colloidal microparticles were prepared via two different strategies. In the first strategy, thermoresponsive PDEGMA was physically adsorbed onto the surface of PS microspheres, whereas, in the second strategy, PDEGMA was chemically grafted from functionalised PCMS microspheres via SI-ATRP. The most simple method i.e. physical adsorption is rapid and can be adapted to many microparticle surfaces but has the drawback of possible desorption of polymer chains during extended use. The chemical grafting method i.e. the formation of covalent bonds between the polymer corona and the microparticle core provides robust and well defined materials but is more complex and time-consuming. In both cases, particle aggregation in their suspensions occurred on increasing the temperature to above the LCST of PDEGMA, but could be reversed by cooling the suspensions back to below the LCST. This confirmed the presence of the thermoresponsive polymer on the surface of the microspheres using both methods (adsorption and grafting). Rheological measurements demonstrated that the viscoelasticity of the prepared particle gels can be tuned, enabling these gels to have the mechanical properties that should facilitate their applications as 3D cell scaffolds for in vitro expansion of cells. Cell culture studies showed that these microparticle based scaffolds can support expansion of clinically relevant cell types (human MSC) and allowed efficient cell recovery after proliferation without the need for using trypsin or enzymatic treatment. Overall, those results suggest that the designed scaffolds had great potential for 3D in vitro cell expansion. The new developed materials have excellent biocompatibility, allow simple and rapid cell seeding and cell recovery after expansion, and possess mechanical strength and stability to support cell growth and proliferation. The materials developed and studied in this thesis may represent a significant contribution to the fields of biomaterials, tissue engineering, 3D cell culture and even bio-separation.